Factores relacionados al síndrome de Burnout en el personal de salud del Hospital Regional Huánuco - López Tuesta, Bryan (2018)
Introduction: The objective of the present study was to determine the relationship of the factors related to burnout syndrome in health staff Hermilio Valdizán Regional Hospital in the period 2014. Methods: Observational study. Having as variables of study: Burnout syndromes, profession, work time in the institution, weekly work load. A sampling method is not applied; for this study to the entire population of doctors and nurses, comprising a total of 130, of whom 110 agreed to participate in this study was taken. A survey conducted by Maslach, recoletar information for other variables to a survey conducted by researchers was used was used to determine the frequency of burnout syndrome. A database of what I gathered in the Microsoft Excel program, which was introduced and analyzed in SPSS and Epidat software, was developed; Statistical analysis of results was obtained using descriptive statistics: absolute and relative frequencies; and inferential statistics (chi 2, Fisher exact test and Mann Whitney). Results: We found that of the 110 respondents, 3 (2.7%) had burnout and 107 (97.3%) did not submit syndrome. 7.3% had a high degree of emotional exhaustion, 20% presented a medium degree of emotional exhaustion and 72.7% a low degree of emotional exhaustion. 20% evidenced a high degree of depersonalization, 29.1% medium degree of depersonalization and 50.9% a low degree of depersonalization. 29.1% showed a low degree of personal fulfillment, 28.2% medium degree of personal fulfillment and 42.7% a high degree of personal fulfillment. The bivariate analysis was assessed by Chi-square test for qualitative variables, finding a "p" not significant in relation to burnout syndrome for: profession (p = 0.991), time to work in the hospital (p = 0.550), hours working week (p = 0.912). Conclusions: Although no significant evidence of this problem was found in doctors and nurses Regional Hospital Hermilio Valdizán, is strong evidence of a significant portion of health has one or two dimensions altered to burnout syndrome, indicating that these would be at risk in the future develop burnout syndrome itself.